The Edge of Life Human Dignity and Contemporary Bioethics - Kaczor, Christopher; Spicker, Stuart F.; Engelhardt, H. Tristram; Wildes, Kevin Wm.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
The Edge of Life: Human Dignity and Contemporary Bioethics resituates bioethics in fundamental outlook by challenging both the dominant Kantian and utilitarian approaches to evaluating how new technologies apply to human life. Drawing on an analysis of the dignity of the human person, both as an agent and as the recipient of action, The Edge of Life presents a "theoretical" approach to the problems of contemporary bioethics and applies this approach to various disputed questions. Should conjoined twins be split, if the division will end the life of the weaker twin? Was Bush's stem cell research decision morally acceptable? Are the 'quality of life' and 'sanctity of life' ethics irreconcilably incompatible? Accessible to both scholars and students, The Edge of Life focuses particularly on the controversial issues surrounding the beginning and ending of human life, tackling some of the toughest practical questions of bioethics including new reproductive technologies (artificial wombs), stem cell research, abortion and physician assisted suicide, as well as many of its vexing theoretical disputes.
When Does a Human Being Become a Person? -- All Human Beings are Persons -- How is the Dignity of the Person as Agent Recognized? -- An Ethical Assessment of Bush's Guidelines for Stem Cell Research -- Moral Absolutism and Ectopic Pregnancy -- Could Artificial Wombs End the Abortion Debate? -- Solomon's Dilemma -- Capital Punishment and the Catholic Tradition.
Keywords: PHILOSOPHY (GENERAL).; ETHICS; MEDICINE -- PHILOSOPHY; MEDICINE; MEDICAL ETHICS; PHILOSOPHY; ETHICS; THEORY OF MEDICINE/BIOETHICS.; MEDICINE/PUBLIC HEALTH, GENERAL; PHILOSOPHY OF MEDICINE